Passive control of base pressure using cavities in a sudden expansion duct: a CFD approach - Ridwan, R; Zuraidi, Nur Husnina Muhamad; Shaikh, Istiyak Mudassir; Khan, Sher Afghan (Science Press, 2022)
CFD is used to simulate the geometry of a Converging-Diverging (C-D) nozzle that has suddenly expanded into an enlarged duct with a cavity. The Mach number for this study is 1.8, and the area ratio is 2.56. The L/D considered 1, 2, 3, 4, 6, 8, and 10, and the simulated nozzle pressure ratio (NPR) was between 2, 3, 5, 5.75, 7, and 9. 2-D model was created with ANSYS Fluent's Design Modeler. The focus was on the duct's base pressure and wall pressure. D = 16 mm is the diameter of the tube. The results show that the NPR and cavity location from the base wall strongly influenced the base pressure. The primary goal of this project is to investigate the effect of the cavity and its geometry on base pressure using CFD. It is found that the base pressure is a vital function of the nozzle pressure ratio (NPR), the inertia level available to the flow, the duct length, and the ambient pressure. The free stream atmospheric pressure strongly influences the base pressure for low duct length. As for the smaller duct sizes, namely L/D = 1 and 2, the ambient atmospheric pressure will most likely impact the enlarged duct's flow development. Cavity as a passive control seems to become effective once the flow from the nozzle is under-expanded. For an over-expanded nozzle, the passive flow control management in the cavity form is not adequate. Any increase in the cavity size from 3: 3 to 6:3 or 3:6 does not give any encouraging results. Hence, there is no need to use a cavity with a more considerable length. The best geometry seems to be with aspect ratio for the given parameters. It might provide better results when the enlarged duct diameter is increased, as the duct diameter in the present case is 18 mm. The cavity location at 1D seems to be the best option to increase the base pressure, Mach number and cavity aspect ratio strongly influence the base pressure in the wake region.